Proceedings of the 2004 ACM SIGPLAN Symposium on Partial Evaluation and Semantics-Based Program Manipulation 2004
DOI: 10.1145/1014007.1014010
|View full text |Cite
|
Sign up to set email alerts
|

Representation-based just-in-time specialization and the psyco prototype for python

Abstract: A powerful application of specialization is to remove interpretative overhead: a language can be implemented with an interpreter, whose performance is then improved by specializing it for a given program source. This approach is only moderately successful with very high level languages, where the operation of each single step can be highly dependent on run-time data and context. In the present paper, the Psyco prototype for the Python language is presented. It introduces two novel techniques. The first is just… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 17 publications
0
42
0
Order By: Relevance
“…Recent research has shown the advantages of type specialization in JIT compilation [19,10]. However, little research exists on the specialization of interpreters for scripting languages.…”
Section: Motivationmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent research has shown the advantages of type specialization in JIT compilation [19,10]. However, little research exists on the specialization of interpreters for scripting languages.…”
Section: Motivationmentioning
confidence: 99%
“…They used direct calling dispatch techniques in their interpreter to gradually develop a trace JIT of a hot region of code. Rigo's psyco [19] is a run time specialization technique for the Python programming language. It performs run time specialization by need using a mixed execution/specialization phase of execution to specialize JIT code fragments.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to show the difference and impact of a JIT and dynamic optimization for the interpreted PyGirl we use Psyco [9], a just-in-time specializer for Python. Since the current version of Psyco (1.6-1) only emits machine code for 32 bit intel-based systems, we benchmark our code using Psyco on a similar Ubuntu installation with the appropriate 32 bit processor.…”
Section: Benchmark Detailsmentioning
confidence: 99%